2011
DOI: 10.1186/1476-069x-10-49
|View full text |Cite
|
Sign up to set email alerts
|

Associations between ozone and morbidity using the Spatial Synoptic Classification system

Abstract: BackgroundSynoptic circulation patterns (large-scale tropospheric motion systems) affect air pollution and, potentially, air-pollution-morbidity associations. We evaluated the effect of synoptic circulation patterns (air masses) on the association between ozone and hospital admissions for asthma and myocardial infarction (MI) among adults in North Carolina.MethodsDaily surface meteorology data (including precipitation, wind speed, and dew point) for five selected cities in North Carolina were obtained from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 37 publications
4
24
0
2
Order By: Relevance
“…Taking into account these limitations, we argue that the results obtained are congruent with the conclusions of the study by Hanna et al (2011). Bucholz et al (2010) found that the air quality, related with ozone and PM 10 concentrations, was better in cyclonic situations than in anticyclonic ones.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Taking into account these limitations, we argue that the results obtained are congruent with the conclusions of the study by Hanna et al (2011). Bucholz et al (2010) found that the air quality, related with ozone and PM 10 concentrations, was better in cyclonic situations than in anticyclonic ones.…”
Section: Discussionsupporting
confidence: 80%
“…The objective weather type classification by Lamb (1972) has been used, which has also recently been applied to rainfall patterns in the Iberian Peninsula (Fernandez-Gonzalez et al, 2012). Other authors like Hanna et al (2011) have found that certain synoptic air masses (dry tropical, transitional and extreme moist tropical) in conjunction with ambient ozone air levels were associated with increased asthma hospitalizations. In our study, it was very useful to reduce the total number of situations to a smaller, more manageable number for each period in order to achieve plausible conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, reference [24] used the SSC to help identify days in which significant snow cover ablation was observed in the Central Appalachians. Reference [25] used the SSC to identify a relationship between particular air mass types and the number of emergency room visits for individuals suffering from asthma or other respiratory illnesses in North Carolina. Reference [26] incorporated the SSC into an investigation of the climatology of the TR air mass type in the winter season.…”
Section: The Spatial Synoptic Classificationmentioning
confidence: 99%
“…To account for this, spatial synoptic classification (SSC) can be used to group weather patterns using a suite of meteorological parameters into distinct categories [1]. The SSC is becoming more widely used to investigate associations between pollutant levels and mortality; one study found that ozone in conjunction with dry tropical and moist tropical weather types increased the risk of hospitalisation for asthma and myocardial infarction [2].…”
Section: Introductionmentioning
confidence: 99%